In-University Quality Management System of Education Based on the Competence Approach - Nelyubina, Elena G.; Safina, Liliya G.; Panfilova, Lyudmila V.; Kazantsev, Ivan V.; Molchatsky, Sergey L.; Stepanova, Ekaterina S.; Ibrahimova, Sakinya Ab. (International Review of Management and Marketing, 2016)
This article considers the system forming elements of the concept of quality of natural science education in the field of providing educational and research services of higher education. The authors have proposed a model of quality management of the higher education establishment work based on the working processes and the competence approach to education. The basic elements of the model of quality management of higher education establishments’ work based on the working processes and the competence approach to education are defined; the criteria and sub-criteria allocated from the point of view of their development by the levels of perfection or stages of development are set up. The necessity of implementation of the in-university quality management system of the quality of higher education establishment’s work on the basis of the working processes and the competence approach to education is substantiated, based on the principles of the students’ activity and the need to introduce innovative and interactive forms of organization of the educational process by using modern communication and educational technologies. Keywords: educational innovations, higher education, professional competency JEL Classifications: I23, O3